﻿A new fish species of the Danio Hamilton, 1822 the was found in the Ky Son district, the Northern Central province of Nghe An, Vietnam - Hao, Nguyen Van; Hoa, Nguyen Thi; Chay, Mua Ba (Academia Journal of Biology, 2012)
﻿Danio kysonensis Nguyen V.H, Nguyen T.H et Mua B.C sp.nov. Holotype: sample code: NA.09.01.001, L = 97 mm, Lo = 77mm; collected at the spring Nam Khien, Nam Can commune, Ky Son district, Nghe An province at the basin of Lam River on 15 January 2009. Paratype: 7 samples, sample code: NA.09.01.002, L = 96 mm, Lo = 78 mm; NA.09.01.003, L = 88 mm, Lo = 69 mm; NA.09.01.004, L = 72 mm, Lo = 58 mm; NA.09.01.005, L = 83 mm, Lo = 63 mm; NA.09.01.006, L = 95 mm, Lo = 76 mm; NA.09.01.007, L = 99 mm, Lo = 77 mm; NA.09.01.008, L = 88 mm, Lo = 68 mm; Location and time of sampling is like holotype. Diagnostis: D = 2.10; A = 3.11-12; P = I9-10; V = 1.6; C = 19+2. 6 L.l = 3033. Scale in front of the back fin is 14. Scale around the tail is 10. The faucal teeth are in 33-V rows: 2.3.4 - 4.3.2. Ctenoid has the falcate I: 8-10 pieces. Vertebra of the whole body is 30. ﻿Lo = 3.29 H = 3.75 T = 6.17l cd = 8.16ccd. T = 3.43 Ot = 4.10 O = 2.41OO. Desription: The body is quite high and flat by sides. Ventral rim is awrier than the back edge; there is no ventral keel. The head is slightly short; the nucha is low and hollow. The snout is quite pointed. Mouth is large, oblique. Maxillary is slightly semi-concave. The lower jaw has the projection compared with the upper jaw. The lip is moderate; the rear lip groove is interrupted in the middle. Two pairs of small barbels. Eyes large, between the body axis and the first half of the head. The distance between the two eyes is large and flat. Bone around the eyes is developed with sharp spines, which are at the rim of bone in front of eyes and backward; gill comb is sparse and long. Faucal teeth have large stumps with curved and pointed tip. Dorsal fins have weak hard spines, starting before the starting point of anal fins and behind the starting point of the abdomen fins, located between the caudal fin base and the eyes. Pectoral and ventral fins are pointed, not reached to the rear fin base. Anal fin is started nearer the ventral fin base than the tail fin base. The tail fin has the deep lobe deep division. Anus is 1/2 away from anal fins to the rear base of the ventral fins. In complete lateral line, the font is curved and down to the belly, extended to the tail staff. The maw has two compartments. Intestine is shorter than the body length. Color pattern: On top, there are many patterns and dots. Along the body, there are three rows of spots, two upper rows of close small spots, lower rows of round and large spots; to the tail staff, the three rows are merged to form a large black streak and stop at the first half of middle rays of the tail fin. Fins are of orange red. Remarks: Danio kysonensis has two pairs of barbels; complete lateral line and back scales have 10 branched rays; unlike D. kysonensis sp.nov., anus has 11-12 branched rays; lateral lines have 30-33 scales; it is different from D. regina, so anus has 14 branched rays; lateral lines have 32 scales; unlike D. trangi, anus has 14 branched rays, lateral lines with 37-38 scales and unlike D. acquipinnatus in which anus has 11-13 branched rays and lateral lines with 34-35 scales. Distribution: Spring Nam Khien, Nam Can commune, Ky Son district, Nghe An province belongs to Lam River system, in which springs are small, water is clear and running, bed has multiple gravels; fish lives in shoal, eating moss with the maximum size of 15 cm. Etymology: named after kyson district where samples of this species was collected.